Non-surgical management of iatrogenic lateral root perforation: a case report - Lanker, Abid; Fathey, Wessam; Samar, Shereen; M., Zakirulla; Imranulla, Mohamed; Pasha, Shiraz (International Journal of Research in Medical Sciences, 2018)
Perforation is a procedural accident that occurs during root canal treatment, creating an artificial communication between the root canal and the supporting periodontal apparatus. Iatrogenic root perforation is a major complication of endodontic and restorative treatments, leading to impairment of tooth prognosis. Successful management of root perforations is dependent on early diagnosis of the defect, location of the perforation, choice of treatment, materials used, host response, and the experience of the practitioner. This case report presents the successful management of an iatrogenic lateral root perforation in a tooth with radiographic evidence of periodontal healing over one year follow-up.